The Crime of Witchcraft and Vigilante Action (Eigenrichting) - Syamsuddin Syamsuddin; Ridwan Ridwan; Iksan Iksan (Jurnal Daulat Hukum, 2021)
The witchcraft incident in Bima Regency has threatened the safety and security of human life, witchcraft has triggered people to take vigilante actions (Eigenrichting) as a counter reaction by means of destruction, persecution and even murder. This study aims to determine public perceptions related to witchcraft, and also to find out why witchcraft always results in mass vigilante action (Eigenrichting) so that prevention and resolution efforts can be formulated. This study uses empirical or sociological research, data collection is carried out by direct and structured interviews and through literature study, while drawing conclusions using inductive methods. The results showed, first; In the period 2016-2021, there were 53 cases of alleged witchcraft practices in Bima Regency, damaging the social order and disrupting community stability. The community considers witchcraft as a dangerous or evil act, because the motive and purpose of using witchcraft is to torture, and/or kill human souls; Second; The behavior of witchcraft has led to vigilante actions (Eigenrichting) in some people, this is due to the existence of a legal vacuum that has not regulated the act of witchcraft and how to solve it legally. The act of vigilantism (Eigenrichting) appears as a form of reaction that arises from the community due to their rights and comfort being disturbed, which action is manifested in the form of violence as an act of revenge against the perpetrators of witchcraft. The juridical conclusion that the terminology of witchcraft and vigilante acts (Eigenrichting) have not been specifically regulated in the current laws and regulations as prohibited acts and are threatened with punishment. As a suggestion that the terminology and elements of the criminal act of witchcraft in the current Criminal Code Bill need to be expanded further, as well as the system of proving the crime of witchcraft in the Indonesian criminal procedure law needs to obtain further, more complete arrangements.